Evaluating Lateral Transshipment Policy in a Two-Echelon Inventory System - Satyendra, Kumar; Venkata, Rao (Journal of Comparative International Management, 2005)
Abstract Emergency shipments from higher and/or same echelon levels are one of the popular tools to handle the stock-out position at some warehouse. Our paper deals with a lateral stock transshipment model involving one plant and two warehouses, lateral transshipment is considered as an option at each re-order decision under the standard (r,Q) inventory replenishment policy. We focus on incorporating the above stock transfer feature in the order fulfillment decision and designed an simulation to find the effect of lateral stock transfer policy on various parameters viz. average inventory at each warehouse, average number of stock-out days at each warehouse, total cost (comprising of inventory cost, stock-out cost and transportation cost). The experimental results show that the stock transfer policy has the potential to reduce the total cost, average inventory and average stock-out days. We have also compared the cases where information is shared online or with some delay. The delay is because of serial communication between the supply chain players. The results show that there are benefits of no information delay i.e. online information sharing over the case with information delay.